PERAN PENDIDIKAN KARAKTER MELALUI KEGIATAN KEPRAMUKAAN PADA SISWA MI BAHRUL ULUM JAKARTA BARAT: PERAN PENDIDIKAN KARAKTER MELALUI KEGIATAN KEPRAMUKAAN PADA SISWA MI BAHRUL ULUM JAKARTA BARAT - Ihsan, Azam Nur; Magdalena, Ina; Sa’odah, Sa’odah; Sumiyani, Sumiyani; Enawar, Enawar (Jurnal Pendidikan Dasar, 2018)
This qualitative research aims to determine the role of extracurricular scouts in shaping the character of student responsibility and to find out what activities can shape the character of the responsibility of students of MI Bahrul Ulum Jakarat Barat. In this study the authors used descriptive qualitative research. This research was conducted at MI Bahrul Ulum, West Jakarta. Data was collected through observation, interviews, questionnaires and documentation. Analysis of the author's data uses descriptive qualitative by reducing data, displaying data and concluding flexibly in order to answer the existing problem formulation. The results of this study used methods to educate the character of student responsibility is to make habituation, exemplary, giving advice and achieving SKU through routine activities, PERSAMI activities and recreational activities / games. This can be proven by the achievement of 10 indicators of responsibility. Based on the results of questionnaires regarding students 'attitudes in participating in scouting activities in Bahrul Ulum MI, it can be seen from the table that students' attitudes in taking extracurricular scouts have an average range of 61% meaning that most students are responsible for what constitutes their rights and obligations and a small number of students still lack responsibility in participating in scouting activities.